Assessment of the Sediments Contamination by Heavy Metals of the Cheliff River, Algeria.. - Addou, Ahmed; Abdelmalek, Fatiha; Ouddane, Baghdad (My University, 2006)
This study deals with the pollution of the greatest river in Algeria, and, therefore, 180 sediment samples from the Cheliff River from three industrial areas in Tiaret, Relizane and Chlef were analyzed. The concentration of heavy metals was determined by Inductively Coupled Plasma-Atomic Emission Spectrometry (ICP-AES). The results show that the sediment samples were highly polluted, particularly near Chlef and Relizane cities, with Cd (global mean: 5.48±0.27 mg Kg-1 dry weight), Pb (384±19), Zn (1264±63), Cu (442±22) and Cr (399±20). These results clearly exceed the ERL values recommended by US EPA. Due to natural dilution and diffusion, the level of contamination decreases near Tiaret. A comparison with the data of different sites throughout the world, the background values (Shale) and sediment quality guidelines was established. This study reveals that river sediments of Cheliff River are highly contaminated by five heavy metals: Cd, Pb, Zn, Cu and Cr.
Keywords: The Cheliff River, heavy metal, industrial effluent , river sediment, contami nant, statistical analysis.